Mewujudkan Keadilan Ekonomi Melalui Perpuluhan di Era Revolusi Industri 4.0: Realizing Economic Justice Through Tithing in the Era of the Industrial Revolution 4.0 - Yushak Soesilo (Sekolah Tinggi Teologi Baptis Indonesia, 2021)
This article aimed to study the prospect of tithe as an instrument of the church in realizing economic justice. The industrial revolution 4.0 era has resulted in economic inequality, where there are parties who can reap huge benefits from the changing working way, on the other hand there are those who must be eliminated from job competition. In this case the church is called to realize one of the Kingdom of God visions, namely justice. This study was conducted by pastoral circle or practical theological circle method. Through this study, it could be concluded that like zakat among Muslims, tithe is an instrument of the church, of which it is properly managed in accordance with the true spirit of tithing, that has the power to realize economic justice.